Function of Traditional Music Karo Gendang Lima Sedalanen in Implementation of Erpangir Kulau Ceremony - Octaviana Tobing (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Erpangir kulau is a term or name created by the Karo community to express a tradition of religious ceremonies or self-cleansing rituals in the Karo community, which uses Karo traditional music, ensemble Gendang Lima Sedalanen, as a supporting element of its implementation. The purpose of this study was to determine the Function of Traditional Music Karo Gendang Lima Sedalanen in Implementation of the Erpangir Kulau Ceremony. The results showed that the five functions according to the Kustap theory were fulfilled by the use of the ensemble Gendang Lima Sedalanen. In its function as an emotional expression, it can be seen from how the ensemble has a strong energy to bring out the emotions of all the actors involved in carrying out the religious ceremonial activities, so that various attitudes of the ceremonial participants appear. Whereas in its function as a communication is realized during the ongoing communication between guru sibaso  who act as a medium between the spirit that is believed to be present, and the people who carry out pangir. Furthermore, the function of Gendang Lima Sedalanen as a social response arises from how the entire Karo community with various temperaments, but can unite to carry out this ceremony. When it functions as a cultural preservation fulfilled through its use in the ritual Erpangir Kulau ritual, it is a form of appreciation and love for their culture. Finally, in its function as a symbol representation is realized through guru sibaso who is a symbol of someone who has his own expertise or prestige.